Analisis Kebijakan Pengelolaan Pajak Daerah Dalam Meningkatkan PAD di Kota Pematang Siantar - Pawer Panjaitan,; Darwin Damanik,; Savirgi, Savirgi; Octa Saragih,; Hartati Sitio,; Tia Saragih,; Sintong Simanjuntak,; Grace Naibaho, (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The aim of the research conducted by researchers is to determine the extent to which local original income has increased through regional tax management mechanisms. The Regional Revenue Agency is the Department responsible for managing local revenue. For this reason, researchers are interested in conducting research related to "Analysis of Regional Tax Management Policy in increasing PAD in Pematang Siantar City". The method that researchers used in this research was a quantitative, descriptive method with an inductive approach, with data sources obtained from secondary data. Secondary data was obtained from literature reviews, documentation and regulations as well as previous scientific journals. Pematangsiantar City is an autonomous region that does not have natural resources that can be exploited, so local government creativity and innovation is needed to be able to increase PAD from taxes which makes it possible to increase Original Regional Income as an autonomous government continues to strive to mobilize various economic potentials in its region. This is done so that economic actors can participate and actively participate in moving the economy so that they are able to contribute to economic growth in Pematangsiantar City.